EMS naloxone administration as non‐fatal opioid overdose surveillance: 6‐year outcomes in Marion County, Indiana. (26th September 2018) - Ray, Bradley R.; Lowder, Evan M.; Kivisto, Aaron J.; Phalen, Peter; Gil, Harold
Abstract: Background and Aims: Despite rising rates of opioid overdose in the United States, few studies have examined the frequency of non‐fatal overdose events or mortality outcomes following resuscitation. Given the widespread use of naloxone to respond to overdose‐related deaths, naloxone administration may provide a useful marker of overdose events to identify high‐risk users at heightened risk of mortality. We used naloxone administration by emergency medical services as a proxy measure of non‐fatal overdose to examine repeat events and mortality outcomes during a 6‐year period. Methods: We conducted a retrospective investigation of all cases in Marion County, Indiana between January 2011 and December 2016 where emergency medical services used naloxone to resuscitate a patient. Cases were linked to vital records to assess mortality and cause of death during the same time‐period. We used Cox regression survival analysis to assess whether repeat non‐fatal overdose events during the study period were associated with the hazard of mortality, both overall and by cause of death. Results: Of 4726 patients administered naloxone, 9.4% ( n  = 444) died an average of 354 days [standard deviation (SD) = 412.09, range = 1–1980] following resuscitation. Decedents who died of drug‐related causes (34.7%, n  = 154) were younger and more likely to have had repeat non‐fatal overdose events. Patients with repeat non‐fatal overdose events (13.4%, n  = 632) had a ×2.07 [95% confidence interval (CI) = 1.59, 2.71] higher hazard of all‐cause mortality and a ×3.06 (95% CI = 2.13, 4.40) higher hazard of drug‐related mortality. Conclusions: Among US emergency medical service patients administered naloxone for opioid overdose, those with repeat non‐fatal opioid overdose events are at a much higher risk of mortality, particularly drug‐related mortality, than those without repeat events.